Propuesta de un centro de interpretación cultural, para el desarrollo turístico del cantón Arenillas, provincia de El Oro - Alejandro Arboleda, Sebastián Antonio (2023)
In the Arenillas canton is prominent for the touristic diversity profitable economic activity; this is a place endowed by big resources that go from to cultural, natural aspects to permit to reach its touristic development. For these reason in this investigation, it’s proposed general objectives that permits elaborate the proposal of a cultural interpretation center CIC for the touristic development of canton Arenillas, supported by to specific objectives: Diagnosing the touristic resources for the CIC and defining the proposal of CIC for the first objective a diagnostic of the touristic resource was performed through the stop to of the touristic diagnostic of Carla Recourse’s methodology to identify and analyze the tourist resources of the canton, which kept priority through INPC’s data that enter upon archeology, oral traditions, clothing and good chattels. The technical aspects of the survey determined the proposal area where the CIC will be placed additionally, the PESTEL’s analysis permitted to analyze externally the field of study to stablish all the information given in a FODA pattern, and subsequently to define this FODA that stated the strategical objectives which are keys for the development of the second objective in which the plan of needs is stated this plan determine the rooms of the center equipment, interpretative material and scripts based upon the methodology Sam Ham there in this place the tourist signs where stated and finally the internal and external touristic mark of the center was designed determining clear and specific priority’s in which rooms competent for settings its functioning where created; however the deficiencies of GADM damages the cultural touristic development of Arenillas canton, in a majority way, due to this GADM will be considered in the proposal as the main factory for the support of the project.